Wild Sex in Zebrafish: Loss of the Natural Sex Determinant in Domesticated Strains. Issue 3 (18th September 2014) - Wilson, Catherine A; High, Samantha K; McCluskey, Braedan M; Amores, Angel; Yan, Yi-lin; Titus, Tom A; Anderson, Jennifer L; Batzel, Peter; Carvan, Michael J; Schartl, Manfred; Postlethwait, John H
Abstract: Sex determination can be robustly genetic, strongly environmental, or genetic subject to environmental perturbation. The genetic basis of sex determination is unknown for zebrafish ( Danio rerio ), a model for development and human health. We used RAD-tag population genomics to identify sex-linked polymorphisms. After verifying this "RAD-sex" method on medaka ( Oryzias latipes ), we studied two domesticated zebrafish strains (AB and TU), two natural laboratory strains (WIK and EKW), and two recent isolates from nature (NA and CB). All four natural strains had a single sex-linked region at the right tip of chromosome 4, enabling sex genotyping by PCR. Genotypes for the single nucleotide polymorphism (SNP) with the strongest statistical association to sex suggested that wild zebrafish have WZ/ZZ sex chromosomes. In natural strains, "male genotypes" became males and some "female genotypes" also became males, suggesting that the environment or genetic background can cause female-to-male sex reversal. Surprisingly, TU and AB lacked detectable sex-linked loci. Phylogenomics rooted on D. nigrofasciatus verified that all strains are monophyletic. Because AB and TU branched as a monophyletic clade, we could not rule out shared loss of the wild sex locus in a common ancestor despite their independent domestication. Mitochondrial DNA sequences showed that investigated strains represent only one of the three identified zebrafish haplogroups. Results suggest that zebrafish in nature possess a WZ/ZZ sex-determination mechanism with a major determinant lying near the right telomere of chromosome 4 that was modified during domestication. Strains providing the zebrafish reference genome lack key components of the natural sex-determination system but may have evolved variant sex-determining mechanisms during two decades in laboratory culture.